Studi Penerapan Sistem Manajemen Kesehatan dan Keselamatan Kerja (SMK3) di RSUP Dr. Sardjito Yogyakarta - Ullya Rahmawati; Muryoto Muryoto; Iswanto Iswanto (Sanitasi: Jurnal Kesehatan Lingkungan, 2010)
The management system on occupational health and safety (SMK3) should be implemented as well in hospitals. The ministry of labour's regulation No.05/ Men/ 1996 states that all industries, included hospitals, which has potentiality of health risk should applying the system. This study was aimed to understand the effectivity of SMK3 implementation and its relationship with occupational accidents in DR Sardjito General Hospital between 2004-2007 by conducting a survey based descriptive study. The data were collected using check list for auditing the re- lated documents and conducting indepth interview with the head of in-patient care wards. The results show that the score of SMK3 implementantion was 93,97 % or at a very good level. The highest frequency rate was 1,44 in 2004, and the lowest was 0,24 in 2007. It can be concluded that the implementation of SMK3 in DR Sardjito General Hospital is assessed as good and effective. However, more attention should be paid to unreported accidents which becoming the primary finding in the audit. Furthermore, external audit and sertification in the future should be planned and implemented.